Pengaruh Electronic Word of Mouth terhadap Travel Intention Wisatawan ke Nuart Sculpture Park Bandung - Fauziah Nurfitri; Dwiesty Dyah Utami (Universitas Negeri Medan, 2020)
This study aims to determine how electronic word of mouth (eWOM) on TripAdvisor affects travel intention of tourists to Nuart Sculpture Park Bandung. The problem in this study is focused on the influence of eWOM on tourist travel intention due to the current development of the internet helps tourist destinations to market their products. In addition, TripAdvisor was chosen in this study as a platform that has a role as a very popular online travel review site by displaying reviews from tourists and can be read by other travelers. To approach this problem, this study uses Ajzen’s statement (2015) which mentions that travel intention can be predicted from 3 factors, namely behavioral beliefs, normative beliefs, and control beliefs. This research uses descriptive quantitative method, by distributing questionnaires to 100 respondents, and analyzed using descriptive statistical data analysis techniques along with simple linear regression. This study concludes that tourist travel intention can be influenced by electronic word of mouth by 61.1% while 38.9% is influenced by other factors.